2016
DOI: 10.1002/sd.1615
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Consumption of Groceries: the Importance of Believing that One Can Contribute to Sustainable Development

Abstract: This study investigated relations between consumers' sustainable development self-efficacy, attitudes, norms and intentions to purchase sustainable groceries such as ecological and fair trade foods. Demographic variables were also investigated. Attitudes and norms were positively associated with intentions to purchase sustainable products. The importance of different types of attitudes and norms for explaining sustainable consumption depended on the facet of purchasing intentions that was investigated. Self-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
99
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 44 publications
10
99
3
5
Order By: Relevance
“…This was contrary to our hypothesis and to the findings of two prior studies that investigated different components of self-efficacy in connection with sustainable consumption in everyday life (Hanss & Böhm, 2010;Hanss et al, 2016). A possible explanation for this might be that travel decisions (as conceptualized in this study) are often made in private and are therefore less socially visible than everyday consumer choices, which were the focus in the aforementioned studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This was contrary to our hypothesis and to the findings of two prior studies that investigated different components of self-efficacy in connection with sustainable consumption in everyday life (Hanss & Böhm, 2010;Hanss et al, 2016). A possible explanation for this might be that travel decisions (as conceptualized in this study) are often made in private and are therefore less socially visible than everyday consumer choices, which were the focus in the aforementioned studies.…”
Section: Discussioncontrasting
confidence: 99%
“…While they found that both components were positively associated with sustainable purchase habits, selfefficacy towards indirectly influencing the environment (through encouraging other consumers) explained more variance than self-efficacy towards directly influencing the environment (through own consumer choices). Hanss et al (2016) reported similar results, and furthermore, found self-efficacy (direct and indirect) to explain greater variability in intentions to purchase sustainable groceries than any other investigated variable (attitudes, norms, and demographics). Accordingly, we expect that people distinguish between beliefs about the direct and beliefs about the indirect environmental impact of their travel choices, and that the latter shows the stronger association with intentions.…”
Section: Efficacy Beliefssupporting
confidence: 60%
See 1 more Smart Citation
“…Research shows that these beliefs are also important for explaining variability in consumption motivated by sustainability concerns. For instance, consumers who believe that they can personally promote sustainability goals through their purchases also seem more likely to buy sustainable instead of conventional product alternatives, than consumers who question their abilities in this regard (e.g., [16][17][18]). Different lines of research have used different terms to refer to these types of personal beliefs [17].…”
Section: Social Comparison Feedback and Perceived Efficacymentioning
confidence: 99%
“…For instance, consumers who believe that they can personally promote sustainability goals through their purchases also seem more likely to buy sustainable instead of conventional product alternatives, than consumers who question their abilities in this regard (e.g., [16][17][18]). Different lines of research have used different terms to refer to these types of personal beliefs [17]. The present paper builds on the literature that construes issues of environmental sustainability as social dilemmas (e.g., [19]), and uses the term self-efficacy to refer to an individual's perceived ability to personally contribute to collectively-beneficial outcomes (here: improvements in sustainable development; see also [20]).…”
Section: Social Comparison Feedback and Perceived Efficacymentioning
confidence: 99%